Réponses

2013-10-29T18:33:22+01:00
Bonsoir

a/ x +10 = 3
x = 3 -10 et x = -7

b/ -7x = 28 donc x = -4

c/ 3x = 0 et x = 0

d/ -21x = 9 donc x = -9/21 ou -3/7

e/ (3x +2)(-7x -3) = 0
ou 3x +2 = 0 donc 3x = -2 donc x = -2/3
ou -7x -3 = 0 donc -7x = 3 d'où x = -3/7

f/ (x-1)(x+4) = (x-2)(x+3)
x² +4x -x -4 = x² +3x -2x -6
x² -x² +4x -x -3x +2x = -6 +4
2x = -2 et x = -1

g/ (3-x)(4+x) +2x -6 = 0
je coince

h/ 2x² -x +1 = x +1
2x² -x -x = 1 -1
2x² - 2x = 0
x = 0
Merci beaucoup j'ai galérai sur cette exercice :p
2013-10-29T21:09:22+01:00
Coucou,

je te mets la réponse en pièce jointe !

Voilà ;)